PELAKSANAAN PEMBELAJARAN TAHFIZH ALQUR'AN BAGI DIASPORA INDONESIA DI MESJID NABAWI MADINAH - Gunawan Simbolon, Hendra; Abd. Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The learning of Al-Qur'an memorization for the Indonesian diaspora at the Prophet's Mosque in Medina has different characteristics from the learning of tahfizh in formal educational institutions. These differences arise from the diverse backgrounds of the participants and the learning context that takes place in an international prayer room. The purpose of this research is to explain how Al-Qur'an memorization instruction was implemented for the Indonesian diaspora at the Prophet's Mosque in Medina. It will include implementation time, learning strategies, media used, and memorizing assessment models. This research employs a descriptive qualitative methodology, gathering data via documentation, interviews, and observation. Tahfizh teachers and members of the Indonesian diaspora who actively engage in tahfizh activities made up the purposefully chosen study subjects. Data reduction, data presentation, and conclusion-drawing were the phases of data analysis, and source and method triangulation was used to assess the validity of the data. The results of the study indicate that Al-Qur'an memorization learning is carried out flexibly without a standard formal schedule, with the main methods being talaqqi, takrir, muroja'ah, and tasmi'. The learning media used are relatively simple: a standard Medina mushaf and audio recitation media. Evaluation is conducted formatively through ongoing memorization, with an emphasis on recitation quality and tajwid accuracy. This memorization learning has proven to be adaptive, contextual, and holistic in supporting the sustainability of Quran memorization among the Indonesian diaspora.